A Comparative Study of the Educational Philosophy of Fazlur Rahman and Ibnu Khaldun - Nugroho, Hani Agustin (Bestari, 2023)
The objective of this work is to juxtapose the educational ideologies of Fazlur Rahman and Ibnu Khaldun. Indeed, these two individuals hold contrasting perspectives on Islamic education. Fazlur Rahman, an Islamic reformer, holds a philosophical perspective on the historical progression of Islamic education. Fazlur Rahman has contributed alternative ideas for Muslims in the contemporary period, particularly in the realm of Islamic education. Rahman views education as primarily focused on the hereafter and mostly defensive in nature, aiming to protect Muslims against the impact of Western culture that poses a challenge to traditional Islamic ethics. Islamic education plays a crucial role in uplifting the most disadvantaged segments of society by addressing poverty, ignorance, social inequity, and helplessness. Conversely, Ibn Khaldun, a prominent Islamic intellectual who greatly impacted the advancement of science, regarded education as a means to safeguard the future of society. According to Ibnu Khaldun, the primary obstacle in education is in the ability to cultivate high-caliber human capital.